Interaction of the Operator of the Tryptophan Operon with Repressor - Rose, John K. (1974)
Transcription studies in vitro on repression of the tryptophan operon of Escherichia coli show that partially purified trp repressor binds specifically to DNA containing the trp operator with a repressor-operator dissociation constant of about 0.2 nM in 0.12 M salt at 37°, a value consistent with the extent of trp operon regulation in vivo. The half-life of the trp repressor-trp operator complex is less than 2 min in vitro in 0.12 M salt.